LEGAL PROTECTION OF THE NAME OF THE US COOPERATIVE OFFICIAL IDENTITY OF THE LEGAL ENTITY - Zulhendrawan; Felly Faradina; Dini Dwi Heniarti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to determine the mechanism for registering the name of a Cooperative as the official identity of a Cooperative legal entity and the limitations of legal protection for the name of a Cooperative in the Indonesian cooperative legal system. The name of the Cooperative is the official identity of a Cooperative legal entity. In the business world, the name of a Cooperative has economic value, because it is able to show the image of the business and influence competitiveness in business. Because of the importance of the name of a Cooperative, it needs legal protection, because there are still names of Cooperatives that are similar and different from the data in the legal entity administration system of the Ministry of Law. This study uses a normative legal approach method, with a statute approach. Legal protection for the name of the Cooperative has not been specifically regulated, such as legal protection for trademark holders in Intellectual Property Rights, so it is necessary to conduct research on legal protection for the name of the Cooperative as the official identity of the legal entity. Based on the results of the study, it is known that legal protection for the name of the Cooperative is given if it has met the material and formal requirements regarding the mechanism for registering the approval of the name of the Cooperative in accordance with laws and regulations. Protection is provided in two ways, namely preventive and repressive. The legal protection given to the owner of a registered Cooperative name is limited to the Cooperative name as the official identity of the legal entity, not as a trademark ownership entity.